Ethnolinguistic diversity within Australian schools: call for a participant perspective in teacher learning. Issue 3 (1st September 2016) - Liyanage, Indika; Singh, Parlo; Walker, Tony
Abstract: Enactment of policy on diversity and learning in Australian schools is evident in "diversity talk" in daily discourses of school teachers. From policy documents to daily staffroom conversations, there is extensive use in contemporary Western educational discourse of ethnolinguistic categories. The categorization of students to groups on the basis of cultural and linguistic attributes can potentially be counter-productive to school learning and broader practices of intercultural understanding. In this paper we critique policy-derived categorizations in Australia that encourage teachers' perceptions of themselves as outside, rather than as participants in, the dynamic interplay of variables that characterize contemporary society. We call for increased opportunities in teacher education and teacher professional development in the areas of cultural identity and shifting cultural ethnoscapes as a basis for contextually responsive and pedagogically viable enactment of procedures and practices mandated by current policy settings with the aim of students from ethnolinguistically diverse backgrounds achieving their potential as participants in the broader community.